1985
DOI: 10.1037/h0080063
|View full text |Cite
|
Sign up to set email alerts
|

Skill in sport.

Abstract: This paper analyzes sport skill from an "expert" perspective. Data are presented to illustrate similar chunking and categorizing performance for sport experts to that found for experts in traditional cognitive skills. Extending the analysis to the acquisition of motor skill again suggests a parallel between sport and cognitive skill; that is, that motor skills become proceduralized. The nature of what proceduralization entails for the motor system is considered. Rather than being creatures in possession of sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0
8

Year Published

1999
1999
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(53 citation statements)
references
References 23 publications
2
43
0
8
Order By: Relevance
“…Já sobre a capacidade de detecção de sinais importantes, os estudos sobre esta variável, foram primeiramente desenvolvidos por Allard e colaboradores, no decorrer da década de 1980 (2,3,4) . Estes estudos apontam que a detecção de sinais é uma função da atenção responsável pela detecção do surgimento de determinado estímulo.…”
Section: Habilidades Perceptivo-cognitivas E Tomada De Decisãounclassified
See 1 more Smart Citation
“…Já sobre a capacidade de detecção de sinais importantes, os estudos sobre esta variável, foram primeiramente desenvolvidos por Allard e colaboradores, no decorrer da década de 1980 (2,3,4) . Estes estudos apontam que a detecção de sinais é uma função da atenção responsável pela detecção do surgimento de determinado estímulo.…”
Section: Habilidades Perceptivo-cognitivas E Tomada De Decisãounclassified
“…De modo geral, os estudos desenvolvidos por Allard (2,3,4) identificaram uma maior velocidade dos experts em detectar sinais perceptivos relevantes, evidenciando que, quando as características da tarefa exigem uma elevada velocidade perceptiva, a habilidade de detectar sinais relevantes mais rapidamente é determinante para a tomada de decisão.…”
Section: Habilidades Perceptivo-cognitivas E Tomada De Decisãounclassified
“…Many other domains (e.g., viewing X-Ray slides of the human body: Lesgold et al, 1988;physics problems: Larkin, 1983; photographs of basketball games: Allard and Burnett, 1985; memory for plays in sport: Allard and Stakes, 1991) reveal the same sorts of perceptual differences between experts and novices. Such research on expertise has a number of features in common.…”
Section: Principle 2: Practice Leads To Efficiencies In Knowledge Accessmentioning
confidence: 99%
“…Likewise, expert springboard divers reveal a greater number of connections between nodes, just like experts in problem-solving research (see Huber). Studies using sorting methods have shown that experts classify problems according to underlying functional principles, whereas novices operate more strongly with superficial features (Allard & Burnett, 1985;Russell & Salmela, 1992). Furthermore, questionnaire methods and interviews have revealed the structure and organization of movement knowledge in, for example, tennis (McPherson & Thomas, 1989, McPherson & Kernodle, 2003, Volleyball (McPherson & Vickers, in the part I of this special issue) and basketball (French & Thomas, 1987).…”
Section: Structure Formation In Long-term Memorymentioning
confidence: 99%